2014
DOI: 10.5539/ass.v11n1p162
|View full text |Cite
|
Sign up to set email alerts
|

The Model of Formation of Foreign-Language Skills of the Students in Self- Learning Activities

Abstract: The article is aimed to develop the model of the formation of foreign-language skills of the students in selflearning activities. The leading approach to the development of this model is the competence approach, reinforcing the role of experience and practical application of knowledge competencies in self-study of foreign language by students. This article presents the following components of the model of formation of foreign-language competencies of students in self-learning activities: goals, objectives, pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The research among Japanese students at American universities showed that the greatest shortage is in the field of communication and interactive and presentation competences [16]. There is a demand for strengthening the role of experience and practical knowledge during foreign language studies as well as emphasis on communication abilities [10]. Finding new approaches, methods and means of creation of foreign language communicative competences of future university foreign language teachers is important [6].…”
Section: Introductionmentioning
confidence: 99%
“…The research among Japanese students at American universities showed that the greatest shortage is in the field of communication and interactive and presentation competences [16]. There is a demand for strengthening the role of experience and practical knowledge during foreign language studies as well as emphasis on communication abilities [10]. Finding new approaches, methods and means of creation of foreign language communicative competences of future university foreign language teachers is important [6].…”
Section: Introductionmentioning
confidence: 99%